2006
DOI: 10.2337/db06-0774
|View full text |Cite
|
Sign up to set email alerts
|

Probe-Independent and Direct Quantification of Insulin mRNA and Growth Hormone mRNA in Enriched Cell Preparations

Abstract: Task division in multicellular organisms ensures that differentiated cell types produce cell-specific proteins that fulfill tasks for the whole organism. In some cases, the encoded mRNA species is so abundant that it represents a sizeable fraction of total mRNA in the cell. In this study, we have used a probe- and primer-free technique to quantify such abundant mRNA species in order to assess regulatory effects of in vitro and in vivo conditions. As a first example, we were able to quantify the regulation of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…Beta cells, like plasma cells and thyroid cells, have a high protein load [32,33], synthesising large quantities of (a single) protein. Proinsulin represents up to 20% of the total mRNA and 30-50% of the total protein synthesis of the beta cell [18,19]. These percentages increase further, when considering only cargo (secretory and membrane) proteins synthesised by the beta cell.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Beta cells, like plasma cells and thyroid cells, have a high protein load [32,33], synthesising large quantities of (a single) protein. Proinsulin represents up to 20% of the total mRNA and 30-50% of the total protein synthesis of the beta cell [18,19]. These percentages increase further, when considering only cargo (secretory and membrane) proteins synthesised by the beta cell.…”
Section: Discussionmentioning
confidence: 73%
“…Proinsulin synthesis represents 30-50% of the total protein synthesis of the beta cell [18,19]. In addition, glucose stimulates proinsulin translation [20], as well as increasing the stability of pre-proinsulin and transcription of the insulin gene [21,22], further increasing the protein load.…”
Section: Introductionmentioning
confidence: 99%
“…Disulfide bond formation in the ER is accompanied by the formation of equimolar amounts of H 2 O 2 as a byproduct (7). In particular in specialized secretory cells, such as pancreatic ␤-cells with insulin as the major biosynthetic product accounting for ϳ50% of total protein synthesis (33,34), the H 2 O 2 generated during the oxidative folding of (pro)insulin could be potentially harmful to the ␤-cell. However, recently, it has been suggested that exogenously added or enzymatically produced H 2 O 2 could contribute either non-enzymatically or via an enzymatic reaction to native disulfide formation (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA from mouse pancreatic islets, acini and whole tissues was extracted and mRNA quantification was performed using Affymetrix mouse 430 2.0 expression microarrays as described (36).…”
Section: Methodsmentioning
confidence: 99%